The process of constructing ontological meaning based on criminal law verbs - Felices Lago, Ángel (Círculo de Lingüística Aplicada a la Comunicación, 2016)
This study intends to account for the process involved in the construction of the conceptual meaning of verbs (#EVENTS) directly related to legal aspects of terrorism and organized crime based on the evidence provided by the Globalcrimeterm Corpus and the consistent application of specific criteria for term extraction. The selected 49 concepts have eventually been integrated in the Core Ontology of FunGramKB (Functional Grammar Knowledge Base), a knowledge base which is founded on the principles of deep semantics and is also aimed at the computational development of the Lexical Constructional Model (www.fungramkb.com). To achieve this purpose, key phases of the COHERENT methodology (Periñán Pascual & Mairal Usón 2011) are followed, particularly those which involve the modelling, subsumption and hierarchisation of the aforementioned verbal concepts. The final outcome of this research shows that most of the apparently specialised conceptual units should eventually be included in the Core Ontology instead of the specific Globalcrimeterm Subontology, due to the fact that the semantic content of their corresponding lexical units can be found in widely used learner`s dictionaries and, consequently, this conceptual information is not only shared by the experts in the field but also by the layperson and the average speaker of the language.